Benefits of Huangqi Herbal Treatment for Patients with Diabetes Mellitus - Theresia, Maria; Priskila, Onny; Mellisa, Mellisa; Aldo, Alfredo; Purnomo, Evelyn (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Diabetes mellitus (DM) is a metabolic disorder caused by abnormalities in insulin secretion and an imbalance between insulin supply and demand. In Traditional Chinese Medicine (TCM), diabetes mellitus is better known as Xiao Ke. In TCM, Xiao Ke disease is caused by internal heat exhaustion deficiency, and one of the traditional treatments for diabetes is the herbal Huang Qi (Radix astragali). Method: This research is a case study, where the researcher makes an in-depth observation of the use of Huang Qi herbs in diabetes mellitus patients. Result and Discussion: The results of diabetes treatment in the initial observation of the patient's blood sugar were 152 mg/dL, and in week 4, it decreased to 86 mg/dL. Isoflavonoids, saponins, and polysaccharides are the three main types of beneficial compounds that have pharmacological activity and therapeutic efficacy in many diseases, one of which is diabetes. In TCM, Huang Qi is beneficial for tonifying Qi and strengthening Yang in spleen Qi deficiency so that the spleen can increase its effectiveness in transformation and transportation. Conclusion: The results of the treatment of diabetes mellitus, or Xiao Ke, using Huang Qi herbs are proven to be able to reduce blood sugar levels in diabetics.